Rates of distribution of psychiatric disorders, hepatitis seroprevalence and illicit substance usage among adults aged 50 years and over in Turkey: a regional representative study - Catak, Zekiye; Uzmez, Emel; Ozturk, Nefise; Ugur, Kader; Aydin, Suleyman (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2019)
Objective: This study examined the major admission etiologies (according to ICD-10 codes), illicit drug use rates and hepatitis seroprevalence of patients 50 age and over admitted to a mental hospital in Elazig, Turkey. Methods: The medical records of 2608 outpatients/inpatient aged >= 50 years admitted to a mental hospital in Elazig between January 01st 2016 and September 30th 2018 were retrospectively examined. Results: Rates of admission etiologies were as follows; for the patient group without any psychiatric diagnosis, followed by recommendation without any medical treatment because of non-specific psychiatric complaints (general examinations, 22.7%), alcohol/substance analyzes (17.6%), bipolar disorders (14.3%), schizophrenia (13.7%) and depression (13.2%). In the 50-59 years age group, the most common reason for admission was alcohol/drug screening for probation and forensic evaluation (20.4%). In the 60-69 and >70 years age groups, depression was the most common admission reason (16.7% and 22%, respectively). Cannabinoids were the most frequently detected substance (11.4% of patients), followed by opiates (3.8%), benzodiazepines (3.5%), amphetamines (2.2%) and cocaine (1.8%). Anti-HBs, HBsAg and anti-HCV were detected as positive by 51.2%, 5.4% and 1.3%, respectively. Anti-HCV rate of substance-depended patients was significantly higher than in the entire study population. Discussion: This study showed that alcohol/substance analysis was more common among people aged 50 years and older than bipolar disorder, schizophrenia and depression. It was found that cannabinoids were detected in 11.4% of the drug analyzes in individuals aged 50 years or older and the anti-HCV ratios of patients receiving treatment at the substance addiction center were higher than the other patients.
Türkiye’de 50 yaş ve üstü yetişkinler arasında psikiyatrik bozuklukların, hepatit seroprevalansının ve yasa dışı madde kullanım oranlarının dağılımı: Bölgesel temsili bir çalışma
Keywords: serology; elderly; substance use; hepatitis; depression; psychiatric disorder